Structural and biochemical analysis of a phosin from Streptomyces chartreusis reveals a combined polyphosphate‐ and metal‐binding fold. Issue 15 (17th June 2019) - Werten, Sebastiaan; Rustmeier, Nils Hinnerk; Gemmer, Maximilian; Virolle, Marie‐Joëlle; Hinrichs, Winfried
Abstract : X‐ray crystallographic analysis of a phosin (PptA) from Steptomyces chartreusis reveals a metal‐associated, lozenge‐shaped fold featuring a 5–10 Å wide, positively charged tunnel that traverses the protein core. Two distinct metal‐binding sites were identified in which the predominant metal ion was Cu 2+ . In solution, PptA forms stable homodimers that bind with nanomolar affinity to polyphosphate, a stress‐related biopolymer acting as a phosphate and energy reserve in conditions of nutrient depletion. A single protein dimer interacts with 14–15 consecutive phosphate moieties within the polymer. Our observations suggest that PptA plays a role in polyphosphate metabolism, mobilisation or sensing, possibly by acting in concert with polyphosphate kinase (Ppk). Like Ppk, phosins may influence antibiotic synthesis by streptomycetes. Abstract :